1983
DOI: 10.1002/1097-0142(19830815)52:4<626::aid-cncr2820520409>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of adriamycin with and without dimethyl triazenoimidazole carboxamide in advanced uterine sarcomas

Abstract: Various drug combinations including Adriamycin have been tested in soft tissue sarcomas, but optimal treatment remains unclear. We have evaluated Adriamycin with and without dimethyl‐triazeno‐imid‐azole‐carboxamide (DTIC) in the treatment of Stage III or IV and recurrent sarcomas of the uterus. Two hundred and forty cases of these rare tumors were evaluable. Of 146 evaluable patients with measurable disease, 13/80 (16.3%) of Adriamycin‐treated patients and 16/66 (24.2%) of patients receiving the combination sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0
4

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(136 citation statements)
references
References 12 publications
2
130
0
4
Order By: Relevance
“…Negligible activity was observed in phase II trials testing the following drugs as single agents: cisplatin, mitoxantrone, amonifide, oral etoposide, diazoquone (AZQ), intravenous etoposide, topotecan, paclitaxel, thalidomide, and trimetrexate [3][4][5][6][7][8][9][10][11][12][13][14]. Single agents that show moderate activity in leiomyosarcoma include ifosfamide (response rate 17.2%), doxorubicin (response rate 25%), and gemcitabine (bolus infusion achieved a 20% response rate among women with uterine leiomyosarcoma who had received 0-1 prior cytotoxic regimen) [15][16][17]. Trabectedin achieved a response rate of 8% among patients with prior treatment, and 17% as first-line therapy, in patients with soft tissue sarcoma [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Negligible activity was observed in phase II trials testing the following drugs as single agents: cisplatin, mitoxantrone, amonifide, oral etoposide, diazoquone (AZQ), intravenous etoposide, topotecan, paclitaxel, thalidomide, and trimetrexate [3][4][5][6][7][8][9][10][11][12][13][14]. Single agents that show moderate activity in leiomyosarcoma include ifosfamide (response rate 17.2%), doxorubicin (response rate 25%), and gemcitabine (bolus infusion achieved a 20% response rate among women with uterine leiomyosarcoma who had received 0-1 prior cytotoxic regimen) [15][16][17]. Trabectedin achieved a response rate of 8% among patients with prior treatment, and 17% as first-line therapy, in patients with soft tissue sarcoma [18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Omura et al (9) investigated the efficiency of ADM + DTIC therapy and reported that, among 66 cases with measurable lesions of uterine sarcoma, 16 (24.2%) achieved a remission (CR + PR). Specifically, the response rate was 30.0% (6/20) in cases with LMS.…”
Section: Discussionmentioning
confidence: 64%
“…Rational therapeutic regimens for metastatic soft-tissue sarcomas have not been established. ADR is the most effective single agent, with a response of 16-27% for treatment of soft-tissue sarcomas [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Large randomized studies, comparing ADR-based combination chemotherapy regimens with single-agent ADR, have been reported. In some of these trials response was greater in the combination chemotherapy arms [6][7][8] whereas in others primary outcomes were not significantly different between treatments. MAID, which we chose in this case, is a recommended combination regimen for softtissue sarcoma according to the National Comprehensive Cancer Network guidelines [9].…”
Section: Discussionmentioning
confidence: 99%